2020
DOI: 10.1177/2377960820925959
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experimental Study of a Basics of Evidence-Based Practice Educational Intervention for Health and Social Care Professionals

Abstract: Education is one of the central interventions to promote evidence-based practice (EBP) in service organizations. An educational intervention to promote EBP among health and social care professionals was implemented in a Finnish hospital. The aim of this study was to explore the outcomes of an educational intervention, focusing on the basics of EBP for health and social care professionals, using a quasi-experimental study design. The data were collected with a questionnaire before, immediately after, and 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(110 reference statements)
2
2
0
Order By: Relevance
“…Though commonly used in the field of social work, public health, and education, the difference between pre-and posttest may have been affected by other confounding factors such as history, maturation, and testing effects [ 47 ]. Additionally, the eight-month APTP-RCB program had a dropout rate of 46.7%, similar to the study by Melender et al [ 48 ] who reported a dropout rate of 42.2% after participating in their six month intervention. This may be due to time-consuming and routine workload as frequently encountered in limited health resources settings.…”
Section: Discussionsupporting
confidence: 84%
“…Though commonly used in the field of social work, public health, and education, the difference between pre-and posttest may have been affected by other confounding factors such as history, maturation, and testing effects [ 47 ]. Additionally, the eight-month APTP-RCB program had a dropout rate of 46.7%, similar to the study by Melender et al [ 48 ] who reported a dropout rate of 42.2% after participating in their six month intervention. This may be due to time-consuming and routine workload as frequently encountered in limited health resources settings.…”
Section: Discussionsupporting
confidence: 84%
“…In tandem with students' perception of improved organizational culture and readiness for EBP, over the course of the study, students' EBP beliefs and EBP implementation also improved and were sustained at Time 2 (Leufer et al, 2021 ). This suggests a relationship between these variables and reflects the findings of other similar studies (Breckenridge‐Sproat et al, 2015 ; Cleary‐Holdforth, 2020 ; Gorsuch et al, 2020 ; Melender et al, 2020 ; Melnyk et al, 2017 ; Milner et al, 2018 ; Williams et al, 2015 ; Yoo et al, 2019 ). Findings demonstrated widespread opportunities for intervention, highlighting context‐specific areas that can be targeted and improved, and offering insight into strategies that can be recommended.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests a relationship between these variables and reflects the findings of other similar studies (Breckenridge-T A B L E 1 Organizational culture and readiness for EBP survey • The extent to which clinicians model EBP in their clinical settings. Sproat et al, 2015;Cleary-Holdforth, 2020;Gorsuch et al, 2020;Melender et al, 2020;Melnyk et al, 2017;Milner et al, 2018;Williams et al, 2015;Yoo et al, 2019). Findings demonstrated widespread opportunities for intervention, highlighting context-specific areas that can be targeted and improved, and offering insight into strategies that can be recommended.…”
Section: Williams Et Al (mentioning
confidence: 99%
“…The use of EBP is strongly correlated with better patient outcomes, including shorter hospital stays, lower readmission rates, lower mortality [ 3 ], lower health disparities, and decreased trial and error due to ineffective medical procedures [ 4 ]. Moreover, it aids in the standardization of nursing practices, and the development of nurses’ bodies of knowledge [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%